Cover Crop Management in Semi‐Arid Regions: Effect on Soil and Cash Crop. Issue 5 (7th September 2020) - Jones, Clain; Olson‐Rutz, Kathrin; Miller, Perry; Zabinski, Cathy
Abstract : Fallow‐based cropping systems in semi‐arid regions have been profitable and often less risky than recrop; however, their use is damaging to soil health and may limit long‐run profitability. Cover crops can reduce summer fallow while possibly improving soil health. This article addresses cover crop management impacts on soil organic matter, soil water and N, and subsequent cash crop yields and grain protein concentration. Earn 1 CEU in Soil & Water Management by reading the article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/856 .